SEPARATION OF CERRIUM (IV) FROM MONAZITE VIA TUBULAR SUPPORTED LIQUID MEMBRANE TECHNIQUE USING TRI OCTYLAMINE (TOA) CARRIER - AMALIA (NIM : 20510031); Pembimbing : Dr. Aminudin Sulaeman, MS, VINA
Utilizing rare earth element as the mutual material develops increasingly. In line with the development of science and technology, the demand of rare earth element increases from year to years. China still holds the biggest rare earth metal supply, and there are many countries depend on it. Indonesia is one of the countries which has a potency of rare earth elements, in Indonesia the rare earth element contains in the monazite, it is lantanida thorium fosfat (Ln, TH)PO4 which is an innate mineral in the processing of tin metal. If this potency can be processed, so it is possible to be an economic reserve mineral source. The separating of rare earth element has been being a difficult separation, because the chemical characteristic and physical characteristic from the elements of lantanida group have similarity each other. There are many separation methods conducted to separate rare earth element, among them is solvent extraction and resin ion exchange. However, these both methods still have a shortage, such as it needs more solvents and the lack of selectivity. One of the alternative methods to solve the problem is the technique of separation via supported liquid membrane; this technique is developed from solvent extraction by taking extraction substance (carrier) to a hollow polymer membrane. Carrier compound selection is a main factor determines the success of extraction and separation by using SLM technique. Carrier compound will have a high selectivity if only separates one specie specifically. This research aims to separate cerium (IV) from Bangka monazite via tubular supported liquid membrane technique (TSLM) using TOA carrier. The step of separating process is destruction monazite mineral using KOH alkali, uranium and thorium precipitation, Ce(III) oxidation becomes Ce(IV) by using KMnO4, and separation using liquid membrane supported by tubular membrane. Selection of TOA solution as carrier solution because its characteristic is more selective to separate Ce(IV) from other rare earth element. The feed solution used is a mixture solution of rare earth element which is soluble in over sulphate acid, while the receiver solution used is carbonate sodium solution. To get optimal result of separation, the variation is conducted to the concentration of feed solution, carrier, receiver solution, and analyte concentration in the feed solution. From this research, found that the best condition of cerium (IV) separation is on 0.2 M feed solution sulphate acid concentration, carrier solution TOA 4% concentration, carbonate sodium concentration as receiver solution 0.6 M, and percent transport is better on more low analyte concentration than on high analyte concentration. By using this method it is obtained the percentage that extraction is 90%, for pure cerium (IV) solution 100 ppm. The result of next separation is settled on pH 11 to get its hydroxide compound, then it is added by oxalate acid on pH 5.5 to form oxalate compound, and finally this oxalate compound is calcinated on 400C until the cerium in form of oxide is obtained. To indicate transport affectivity of the cerium within this separation, the analysis of oxide compound is conducted which is resulted using XRF. From the result of rare earth element composition analysis using XRF, it is known that cerium(IV) can be transported well through TSLM technique. In order transport affectivity of TSLM in separating cerium (IV) from REE to be better, it is necessary to conduct furthermore research, for instance, by studying the influence of measuring parameters to transport permeability and the using of mixture TOA carrier with other carriers so it is expected to result the synergic effect.